Effects of aircraft noise on annoyance, sleep disorders, and blood pressure among adult residents near the Orio al Serio International Airport (BGY), Italy - Carugno, Michele; Imbrogno, Pietro; Zucchi, Alberto; Ciampichini, Roberta; Tereanu, Carmen; Sampietro, Giuseppe; Barbaglio, Giorgio; Pesenti, Bruno; Barretta, Francesco; Bertazzi, Pier Alberto; Pesatori, Angela Cecilia; Consonni, Dario (La Medicina del Lavoro, 2018)
Background: Aircraft noise may cause several non-auditory health effects, including annoyance, sleep disorders, hypertension, cardiovascular diseases, and impaired cognitive skills in children. Objectives: To perform a cross-sectional study among adult residents near the Orio al Serio International Airport (BGY), Italy to investigate the association between aircraft noise, annoyance, sleep disorders, blood pressure levels, and prevalence of hypertension. Methods: Residential addresses of subjects aged 45-70 years were geocoded and classified in three groups according to noise levels: